Role of serum lactic dehydrogenase, glutamic oxaloacetic transaminase, creatine phosphokinase, alkaline phospatase, serum phosphorus in the cases of bowel ischemia in acute abdomen - Soni, Nitesh; Bhutra, Shyam; Vidyarthi, Shivaji H.; Sharma, Vivek; Singh, Amit (International Surgery Journal, 2017)
Background: Bowel ischemia is a life-threatening condition which may arise from a number of causes affecting the arterial and venous compartments of the mesenteric circulation. The rapid onset of acute mesenteric ischemia and the potential rapidity with which bowel infarction may occur explain the lethality of this disease. The aim of this study was to evaluate the role of serum lactic dehydrogenase (LDH), glutamic oxaloacetic transaminase (SGOT), creatine phosphokinase (CPK), alkaline phospatase, serum phosphorus in the cases of bowel ischemia in acute abdomen. Methods: Above mentioned serum enzymes were measured preoperatively in the fifty patients of acute abdomen. Biomarker levels were compared in patients between equal two groups on the basis intra operative findings of bowel ischemia and non-bowel ischemia. Results: Preoperative estimated serum levels of all described enzymes found to be significantly elevated in patients of group A (with bowel ischemia) in comparison with group B (with no bowel ischemia). Sensitivity and specificity for elevated levels of S. LDH were 88% and 68%, for SGOT 68% and 80%, for S. ALP 72% and 68%, for S. CPK-MB 76% and 84%, and for S. phosphorus 76% and 68% respectively. Conclusions: Preoperative estimated serum levels of all described enzymes found to be significantly elevated in patients of group A (with bowel ischemia) in comparison with group B (with no bowel ischemia). Sensitivity and specificity for elevated levels of S. LDH were 88% and 68%, for SGOT 68% and 80%, for S. ALP 72% and 68%, for S. CPK-MB 76% and 84%, and for S. phosphorus 76% and 68% respectively.